The Effect of Financial Performance on Company Value with Financial Technology as a Moderating Variable in Banking Companies Listed on the Indonesia Stock Exchange - Resyi Minora; Erni Masdupi (Pusat Publikasi Nusantara, 2025)
Banking companies have a strategic role in maintaining economic stability, but banking companies face challenges in increasing corporate value amid regulatory changes, economic uncertainty, and accelerating digital transformation. This study aims to analyze the influence of financial performance on the value of companies with financial technology (fintech) as a moderation variable in banking companies listed on the IDX for the 2019–2023 period. Financial performance was measured using ROA, NPL, LDR, and BOPO, while company value was proxied by Tobin's Q. The research sample consisted of 43 banking companies with a total of 215 observations, and the analysis was conducted using Moderated Regression Analysis (MRA), using SPSS V 22 as an analysis tool. The results of the study showed that ROA, NPL, LDR, BOPO, financial technology, firm size, and firm age did not have a significant effect on the company's value. However, fintech has been shown to be able to moderate the relationship between ROA, LDR, and BOPO to the company's value significantly, while fintech's moderation in the relationship of NPLs to the company's value shows a significant but negative influence. These findings confirm that fintech adoption plays an important role in strengthening or weakening the influence of financial performance indicators on company value in the banking industry.